Studi Literatur tentang Model-Model Pembelajaran Fiqh - Magnum, Nurbeti (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2019)
Islamic religious education is the most important subject of education in Indonesia, therefore Islamic religious education is studied at various levels of education, from early childhood education, elementary, secondary and higher education. But then teachers often find difficulties in applying the right learning model to Islamic subjects. The selection of learning models will certainly have implications for the approaches, strategies, and methods used by teachers in their teaching. Not only that, the selection of learning models will also affect learning outcomes. So from that a teacher must be really full consideration in choosing the learning model that will be used, for the achievement of learning objectives that have been determined by the teacher and the institution.